Non-linear sweep voltammetry of adsorbed species: theory and a method to determine formal potentials - Kätelhön, F; Compton, R (Royal Society of Chemistry, 2017)
Recent literature revealed the hitherto unexploited opportunities offered by unconventional cyclic voltammetry with non-triangular potential sweeps. We here investigate the implications of such techniques for the equilibrium voltammetry of surface-bound analytes and expose rather counter-intuitive effects: if only slightly different potential waveforms are applied, distinct and characteristic features arise in the voltammogram that can be readily exploited for quantitative analysis. Our work comprises a theoretical analysis and suggests initially a simple method to determine formal potentials.